Observability of frequency shift induced by multielectron polarization in the high-order harmonic generation emitted from CO molecules - Nguyen , Kim-Ngan H.; Trieu, Doan-An; Le , Cam-Tu; Nguyen, Hien T.; Phan, Ngoc-Loan Thi (Communications in Physics, 2025)
Studying the effects caused by core electrons of highly polarizable atoms and molecules is essential since interactions between external fields and matter primarily occur in the outer electron shell, but the contribution of the core electrons has been revealed in recent studies. Therefore, investigating the core-electron polarization effect (MEP) in the high-order harmonic generation (HHG) spectrum of matter when interacting with intense, ultrashort laser pulses has attracted significant attention. In our latest work, we have shown that when interacting with a few-cycle laser pulse, MEP induces significant shifts in the HHG peaks of the CO molecules. However, the laser’s parameter ranges of the laser pulse, allowing the observation of these peak shifts, have not yet been thoroughly examined. In this paper, by simulating the HHG emitted from the CO molecule under interactions with few-cycle laser pulses of different parameters, we demonstrate that the laser pulse duration should be greater than three cycles and less than six cycles. Furthermore, the carrier-envelope phase of the laser pulse should be within the ranges of (2π/3, 7π/6) and (5π/3, 2π). These optimal regions guide experiments in choosing laser settings to observe core-electron effects on the HHG spectrum via peak shifts.